Analysis and Classification of Different Types of Partial Discharges by Harmonic Orders - Hapeez, M. S.; Abidin, A. F.; Hashim, H.; Hamzah, N. R.; Hamzah, M. K. (Elektronika ir Elektrotechnika, 2013)
The genesis of this research work was constituted for the issue of classifying the characteristics of harmonics caused by partial discharge (PD). This work was undertaken based on the hypothesis that the characteristics of the harmonic orders caused by different types of Partial Discharge (PD) can be classified. Experimental work was initially performed and the data obtained from it was validated. This work was then followed by an analysis of the data in order to extract the characteristics of harmonics order and to distinguish information of the harmonics distortion. The findings show that different types of PD produce distinctive harmonics characteristics and distinguishable Total Harmonic Distortion (THD) levels. The outcome of this study show that the hypothesis was precise in stating that different PD types can cause different levels and characteristics of harmonic distortions where in all data obtained were able to be classified. The classification criteria were then tested for accuracy and precision. The results obtained from the classification based on harmonics order characteristics show that 100 % of the PD data tested were identified successfully. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.2545